Implementasi Pendekatan Saintifik di MGMP PAI Tingkat SMP Kota Payakumbuh (Universitas Negeri Padang, 2020)
This research was motivated by the problem of Islamic education teachers at MGMP PAI of Junior High School at Payakumbuh. Most of the teachers feels that they still did not fully understand how to implement the scientific approach in learning procces, which is become the characteristic of the 2013 curriculum in Islamic education learning in schools.The implementation of the 2013 curriculum has entered its 7th year since it was implemented. In the dynamics of its implementation, the 2013 curriculum has undergone renewal and improvement of various things both in terms of policy, substance, and methodology.The 2013 curriculum uses a scientific approach in the learning process, it require some activities include observations, questioning, process data, present data and conclude. These learning activities can be done inside or outside the classroom. So that the learning process is not only fixed in the classroom. In implementing this scientific approach, students get scientific learning experiences. In strengthening the scientific approach, it is necessary to apply learning models such as Inquiry learning, Discovery learning, Problem Based Learning and Project based learning. This research is a field research study with qualitative methods. The research instrument was interviews, in addition we use questionnaires to collect some of supporting data.